An Event Study: Islamic vs Conventional banks stock performance and market efficiency after the World Health Organisation declared COVID-19 a pandemic. - Abdel-Aziz, Khaled (2021)
In the aftermath of the Global Financial Crisis, Islamic banks have grown significantly. The dominant belief for this is due to their performance during the crisis which has made economic agents more conscious of their practices. Free from extreme risk-taking behaviour, Islamic banks exhibit a level of certainty which can be attractive to investors. As such, an event study methodology has been employed to examine the differences in stock market performance between the two types of banks, taking a sample of banks from across Europe, United States, and Islamic banks. Daily stock data was collected for these banks between 31st September 2019 and 31st March 2020. The mean-adjusted returns method was used to compute the average abnormal returns. Similar to the extant literature, the findings suggest that Islamic banks stock performance was relatively better than their conventional counterparts. Cumulative abnormal returns across the 10-day event window for Islamic Banks were found to be on average -24.45%, compared to an average of -33.09% for conventional banks.